GROWTH OPTIMIZATION OF LETTUCE (LACTUCA SATUVA L.) GREEN LOOSE LEAF AND ROMAINE VARIETIES ON THE AEROPONIC SYSTEM - Akbar Pamungkas, Trisekar
High demand of lettuce in Indonesia made lettuce become commodity that has high economic value, so it could increase farmers income. Based on data about lettuce domestic production from 2010 to 2013 amounted to 283,770 tons/year, 280,969 tons/year, 294,934 tons/year and 300,961 tons/year. However, the production of lettuce was decreased in 2011. It was because of the existence of the conversion of agricultural land into settlements and factories. The one solution to overcome this problem is to use an aeroponic cultivation. Aeroponic is a plant cultivation technique that allows plants to hang in the air by spraying nutrient solutions to the plants root directly. The spraying system of nutrient solution on aeroponics can be modified automatically so that it can make the nutrient solution sprayed in accordance with the specified time. On the other hand, lighting on the aeroponic system can be controlled automatically so that the plants can absorb light properly. This research aims to optimize the concentration of nutritional factors and spraying interval of nutrient solutions on the lettuce plant growth (Lactuca sativa L.) green loose leaf varieties and romaine which is cultured on the aeroponics system. This reasearch used a completely random design with 6 treatments combination consisting of the lettuce varieties (green loose leaf lettuce and romaine lettuce), concentration (3 mL/L, 5 mL/L, 7 mL/L) and spray interval of nutrient solution (3 minute off, 5 minute off, and 7 minute off) with 2 replications. Observed parameters of this research are numbers of leaves, stem height, root length, shoot fresh weight, and shoot dry weight. Collected data from observation were analyzed by ANOVA and continued with Duncan test with a significant level of 5% using the IBM SPSS Statistic 26 application. Providing the concentration of the nutrient solution amount of 5 ml/L and the interval of spraying in 2 minutes on, 5 minutes off gives the highest stem with 25.181 cm and 25.088 cm, the most heavy shoot fresh weight with 17.386 gram and 12.949 gram, the most heavy shoot dry weight with 0.979 gram and 0.659 gram for green loose leaf lettuce and romaine lettuce sequentially. The highest number of leaves based on this treatment is green loose leaf with 11.860 leaves. The result show concentration of the nutrient solution amount of 3 ml/L and the interval of spraying the nutrient solution in 2 minutes on and 3 minutes off, gives the longest root length for green loose leaf lettuce and romaine lettuce with 46.038 cm and 46.231 cm. The highest number of leaves based on this treatment is romaine lettuce with 9.090 leaves. In conclusion, the concentration and spraying interval of the optimum nutrient solution on the green loose leaf lettuce growth and romaine lettuce in a row was 5 ml/L and 2 minutes for spraying, 5 minutes for nonspraying.